2007
DOI: 10.1038/ni1468
|View full text |Cite|
|
Sign up to set email alerts
|

Direct extracellular interaction between the early secreted antigen ESAT-6 of Mycobacterium tuberculosis and TLR2 inhibits TLR signaling in macrophages

Abstract: Expression of early secreted antigenic target protein 6 (ESAT-6) by Mycobacterium tuberculosis is associated with lower innate immune responses to infection. Here we show that ESAT-6 inhibited activation of transcription factor NF-kappaB and interferon-regulatory factors (IRFs) after Toll-like receptor (TLR) signaling; inhibition of TLR signaling by ESAT-6 required the kinase Akt. Direct binding of ESAT-6 to TLR2 activated Akt and prevented interaction between the adaptor MyD88 and 'downstream' kinase IRAK4, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
312
2
9

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 339 publications
(329 citation statements)
references
References 50 publications
6
312
2
9
Order By: Relevance
“…The protein moiety of lipoproteins is critical for interaction with TLR2. Immunoprecipitation was used to demonstrate the binding of rMPT83 and TLR2 in the absence of acylation or glycosylation, consistent with previous results showing that the recombinant mycobacterial proteins ESAT6, PPE18, and MPB83 bind to TLR2 (25,65,66). The current findings also are consistent with observations that other LprG and LprA lipoproteins trigger the TLR2-signaling pathway, resulting in the secretion of proinflammatory cytokines, such as TNF-a.…”
Section: Discussionsupporting
confidence: 79%
“…The protein moiety of lipoproteins is critical for interaction with TLR2. Immunoprecipitation was used to demonstrate the binding of rMPT83 and TLR2 in the absence of acylation or glycosylation, consistent with previous results showing that the recombinant mycobacterial proteins ESAT6, PPE18, and MPB83 bind to TLR2 (25,65,66). The current findings also are consistent with observations that other LprG and LprA lipoproteins trigger the TLR2-signaling pathway, resulting in the secretion of proinflammatory cytokines, such as TNF-a.…”
Section: Discussionsupporting
confidence: 79%
“…TLR2 receptors, while acting as sensors for extracellular cues or the endocytic network, drive signaling events in response to recognition of pathogen-associated molecular patterns, including mycobacterial antigens like ESAT-6, PE_PGRS antigens; NOD1 and NOD2 operate as cytosolic sensors initiating signaling pathways upon recognition of diaminopimelic acid and muramyl dipeptide (MDP), components of bacterial peptidoglycan (15)(16)(17)(18)(19)(20). Although TLR2 or NOD receptor-induced signaling events culminate in activation and nuclear translocation of NF-B, transcriptome profiles in response to TLR2 or NOD receptors could markedly diverge.…”
mentioning
confidence: 99%
“…ESAT-6, a member of a unique family of proteins present in M. tuberculosis, probably attenuates the innate immune response by dampening the production of the IL-12 p40, TNF-α and NO (30). Recently, it has been shown that ESAT-6 and some peptides were able to dampen TLR2 signaling by preventing assembly of the cytosolic MyD88-dependent signaling scaffold (31). However, other members of the TLR family could be activated by M. tuberculosis, with or without TLR2 interaction.…”
Section: The Toll-like Receptorsmentioning
confidence: 99%